2012
DOI: 10.1111/j.1365-2672.2012.05335.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and fate of giardia cysts in wastewater treatment plants

Abstract: Summary The present study was conducted to review factors affecting the prevalence and concentration of Giardia in raw wastewater. The removal and inactivation efficiency of Giardia by wastewater treatment technologies was also reviewed. Data published for the prevalence of Giardia in wastewater and the removal by wastewater treatment plants was reviewed. Giardia cysts are highly prevalent in wastewater in various parts of the world, which may reflect the infection rate in the population. In 23 of 30 (76·6%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 60 publications
2
22
0
17
Order By: Relevance
“…Estão entre as principais causas de doenças diarreicas em seres humanos em todo o mundo e são considerados para a Saúde Pública, os mais importantes protozoários patogênicos veiculados pela água, devido à elevada resistência à maioria dos processos convencionais para o tratamento de água potável, resistência ao cloro e a alta infectividade (Putignani e Menichella, 2010;WHO, 2011;Fregonesi et al, 2012). Esses protozoários potencialmente patogênicos também são resistentes à maioria dos processos empregados para o tratamento de esgoto doméstico (Nasser et al, 2012;Nasser, 2016). As formas infectantes destes patógenos estão presentes nas fezes dos hospedeiros infectados, que compõem o esgoto bruto que chega às ETE (Estação de Tratamento de Esgoto), tornando o esgoto doméstico, uma das principais fontes de contaminação dos mananciais (Nasser et al, 2012;Nasser, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Estão entre as principais causas de doenças diarreicas em seres humanos em todo o mundo e são considerados para a Saúde Pública, os mais importantes protozoários patogênicos veiculados pela água, devido à elevada resistência à maioria dos processos convencionais para o tratamento de água potável, resistência ao cloro e a alta infectividade (Putignani e Menichella, 2010;WHO, 2011;Fregonesi et al, 2012). Esses protozoários potencialmente patogênicos também são resistentes à maioria dos processos empregados para o tratamento de esgoto doméstico (Nasser et al, 2012;Nasser, 2016). As formas infectantes destes patógenos estão presentes nas fezes dos hospedeiros infectados, que compõem o esgoto bruto que chega às ETE (Estação de Tratamento de Esgoto), tornando o esgoto doméstico, uma das principais fontes de contaminação dos mananciais (Nasser et al, 2012;Nasser, 2016).…”
Section: Introductionunclassified
“…Esses protozoários potencialmente patogênicos também são resistentes à maioria dos processos empregados para o tratamento de esgoto doméstico (Nasser et al, 2012;Nasser, 2016). As formas infectantes destes patógenos estão presentes nas fezes dos hospedeiros infectados, que compõem o esgoto bruto que chega às ETE (Estação de Tratamento de Esgoto), tornando o esgoto doméstico, uma das principais fontes de contaminação dos mananciais (Nasser et al, 2012;Nasser, 2016).…”
Section: Introductionunclassified
“…Nasser et al (2012) reported that in 23 out of 30 studies, all tested raw wastewater samples were positive for Giardia, at concentrations ranging from 2.3 to 1,000,000 cysts/10 L, showing that Giardia pollution is quite universal and requires effective control to secure the biological safety of reclaimed water. Giardia concentrations in raw wastewater and primary, secondary and tertiary treatment effluents were 1300-36,000, 5330-20,330, 0-320 and 0-21 cysts/10 L, respectively, in three municipal wastewater treatment plants in Beijing, China (Fu et al, 2010).…”
Section: Occurrence Of Giardia In Reclaimed Water Samplesmentioning
confidence: 99%
“…Giardia sp. has been detected in sewage (Gassman and Schwartzbrod, 1991;Nasser et al, 2012) as well as in tertiary treatment effluents after chlorination and chloramination (Nasser et al, 2012;Quintero-Betancourt et al, 2003;Ryu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation